PENGARUH JENIS STEK TERHADAP PANJANG AKAR KLON HIBRID ACACIA (Acacia mangium x A. auriculiformis) - , SORAIDA ASHIROH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Acacia hybrid is the result of a cross between Acacia mangium x A. auriculiformis. This type has several advantages, among other growth is more quick, more often form large and more resistant to various environmental conditions place to grow. In addition to regulatory incorrect having, machinery hybrid also has weaknesses are less couse when prompted by generative because the probability of machinery can produce move cards and rogen than that of carrier. That may constitute one- way only for maintaining genetic discuss with propagation prompted thousands. The aim of the experiment was to now some kind off effect on long extension cutting they Acacia hybrid clon ( Acacia mangium x A. auriculiformis). The research is carried out in the hall loved at Balai Besar Penelitian and Pemuliaan Huta (BBPBTH), Kemenhut RI, Purwobinangun, Pakem, Sleman, Yogyakarta, be the month October till Desember 2013. The design used is incorrect completely randomized design (CRD) with the amount of sample is doomed to 10 for each treatment. Treatment is used in a few custom clon and breed rooting (leafy cuttings, node 1 and node 2) and variables is linear rooting ability and life percentage. Results of this study showed that percentage were to adopt best clon Acacia hybrids is clon Ah 33 and Ah 24, with an average life of 100% percent of the leafy cutting and the best filter based on testing of LSD of node 1 at clon Ah 33 with an average rooting ability 15,5 cm. Until vegetative roproduction hook them were clon in this research is a kind of clon Ah 33 with the tip of a leafy cuttings and node 2.